Comparative Histopathological Evaluation of Pulmonary Arterial Remodeling in Fatal COVID-19 and H1N1 Influenza Autopsy Cases - Sergiy G. Gychka; Sofiia I. Nikolaienko; Nataliia V. Shults; Volodymyr M. Vasylyk; Bohdan O. Pasichnyk; Iryna V. Kagan; Yulia V. Dibrova; Muin Tuffaha; Yuichiro J. Suzuki (COVID, 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused the coronavirus disease 2019 (COVID-19) pandemic that devastated the world. While this is a respiratory virus, one feature of the SARS-CoV-2 infection was recognized to cause pathogenesis of other organs. Because the membrane fusion protein of SARS-CoV-2, the spike protein, binds to its major host cell receptor angiotensin-converting enzyme 2 (ACE2), which regulates a critical mediator of cardiovascular diseases, angiotensin II, COVID-19 is largely associated with vascular pathologies. The present study examined the pulmonary vasculature of COVID-19 patients using large sample sizes and provides mechanistic information through histological observations. We studied 56 postmortal lung samples from COVID-19 patients. The comparative group consisted of 17 postmortal lung samples from patients who died of influenza A virus subtype H1N1. The examination of 56 autopsy lung samples showed thickened vascular walls of small pulmonary arteries after 14 days of disease compared to H1N1 influenza patients who died before the COVID-19 pandemic started. Pulmonary vascular remodeling in COVID-19 patients was associated with hypertrophy of the smooth muscle layer, perivascular fibrosis, edema and lymphostasis, inflammatory infiltration, perivascular hemosiderosis, and neoangiogenesis. We found a correlation between the duration of hospital stay and the thickness of the muscular layer of the pulmonary arterial walls. These results demonstrate that COVID-19 significantly affected the pulmonary vasculature in fatal-course patients, also suggesting the need for careful follow-up in non-fatal cases, at risk of pulmonary hypertension.